A method for preparing grain boundary diffusion sintered NdFeB permanent magnet material
By designing PrGa-rich grain boundary phase and nanopowder in neodymium iron boron permanent magnet materials, combining low-temperature sintering and photocuring diffusion source treatment, the preparation problem of large-sized sintering materials is solved, the magnetic performance and production efficiency are improved, and suitable for high-quality sintering. Large-size products in magnetization direction.
Patent Information
- Application Number
- CN202411434590.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing grain boundary diffusion process is difficult to match the preparation of large-sized sintered NdFeB permanent magnet materials with high magnetization direction, and the curing time is long, which affects material performance and cost control.
By designing the magnet matrix components, a PrGa-rich grain boundary phase is formed, the content of ferromagnetic elements in the grain boundary is reduced, and nanopowder is added to the matrix to increase the grain boundary width, providing diffusion for the development of large-sized sintered NdFeB permanent magnet materials. The channel uses a low-temperature long-term sintering process to refine the grains, combining photocuring diffusion sources and aging treatment.
It significantly improves magnetic performance, especially coercive force, and is suitable for large-sized products with high magnetization direction, saves energy and improves diffusion effect, and is suitable for mass production.
Smart Images

Figure CN118969490B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of NdFeB permanent magnet materials and relates to a method for preparing a grain boundary diffusion sintered NdFeB permanent magnet material. Background Art
[0002] With the continuous development of my country's industrial level, it has occupied a dominant position in the international market in many fields such as wind power generation, new energy power, and intelligent manufacturing. Among them, as a key component of magnetoelectric conversion, sintered NdFeB permanent magnet materials are widely used due to their excellent comprehensive magnetic properties. With the continuous advancement of sintered NdFeB permanent magnet material preparation technology, especially with the gradual popularization of grain boundary diffusion process, it has laid the foundation for achieving material cost control and performance improvement. However, there are still some problems with the grain boundary diffusion process, such as the inability to match the preparation of large-size products with high magnetization direction (8mm and above), and the long curing time after grain boundary diffusion. Summary of the invention
[0003] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and propose a method for preparing grain boundary diffusion sintered NdFeB permanent magnet materials. The magnet matrix composition of the grain boundary diffusion sintered NdFeB permanent magnet material is designed, and a PrGa-rich grain boundary phase is formed by matching a main alloy and an auxiliary alloy to reduce the content of ferromagnetic elements in the grain boundary. Nanopowder is added to the magnet matrix to further increase the grain boundary width, thereby providing a diffusion channel for the subsequent preparation process, which is conducive to the development of large-size sintered NdFeB permanent magnet materials.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] A method for preparing a grain boundary diffusion sintered NdFeB permanent magnet material, comprising:
[0006] (1) Main alloy proportioning, smelting, and powdering to obtain main alloy fine powder; the chemical formula of the main alloy is [(Pr 0.25 Nd 0.75 ) x1 (LR) y1 (HR) 1-x1-y1 ] a1 (TM) b1 (HM) c1 B d1 Fe 100-a1-b1-c1-d, wherein 0.7≤x1≤1, 0≤y1≤0.3, 29.5≤a1≤30.5, 0<b1≤5, 0<c1≤0.3, 0.92≤d1≤0.98, LR is one or more of the light rare earth elements La, Ce, and Y, HR is one or more of the heavy rare earth elements Dy, Tb, Gd, and Ho, TM is one or more of Al, Cu, Co, Mn, and Ga, and HM is one or more of Nb, Zr, Hf, Ti, and V;
[0007] (2) Proportioning, smelting and powdering the auxiliary alloy to obtain auxiliary alloy fine powder; the chemical formula of the auxiliary alloy is Pr x2 (Ga a2 Al b2 Ti 1-a2-b2 ) 1-x2 , where 0.3≤x2≤0.9, 0.1≤a2≤0.7, 0≤b2≤0.5;
[0008] (3) mixing the main alloy fine powder, the auxiliary alloy fine powder and the nano powder, adding the additives and pre-pressing to obtain a pre-pressed embryo body;
[0009] The nano powder is one or more of transition metal carbide nano powder and transition metal oxide nano powder;
[0010] (4) The pre-pressed embryo is subjected to isostatic pressing, sintering, black sheet treatment, diffusion source diffusion, diffusion heat treatment, and aging to obtain grain boundary diffusion sintered NdFeB permanent magnet material.
[0011] Preferably, in (1), Al≤0.5, Ga≤0.3 in TM, and Nb+Zr≤0.1 in HM.
[0012] Preferably, the mass ratio of main alloy fine powder, auxiliary alloy fine powder and nano powder in (3) is (90-99): (0.5-9.5): (0.1-0.5).
[0013] More preferably, the mass ratio of the main alloy fine powder, the auxiliary alloy fine powder and the nano powder is (90-99): (0.5-9.5): (0.1-0.5).
[0014] Preferably, the transition metal carbide nanopowder includes one or more of niobium carbide (NbC), tantalum carbide (TaC), vanadium carbide (VC), zirconium carbide (ZrC), and tungsten carbide (WC);
[0015] The transition metal oxide nanopowder includes one or more of ferroferric oxide, titanium dioxide (titanium dioxide), aluminum oxide, and zinc oxide.
[0016] Preferably, the average particle size of the nanopowder is 10-80 nm.
[0017] More preferably, the average particle size of the nanopowder is 20 to 60 nm.
[0018] Preferably, the auxiliary agent in (3) includes one or more of lubricants, aviation gasoline, and antioxidants.
[0019] More preferably, in (3), the mass ratio of the mixed powder of the main alloy fine powder, the auxiliary alloy fine powder and the nano powder to the lubricant is (0.2-1.2):1; the mass ratio of the mixed powder of the main alloy fine powder, the auxiliary alloy fine powder and the nano powder to the aviation gasoline is (0.2-5):1.
[0020] Preferably, (4) the medium static pressure is 180-220 MPa, and the holding time is 5-60 s.
[0021] Preferably, the sintering temperature in (4) is 1000-1070°C, the sintering time is 6-12h, and the vacuum degree is less than 5×10 -2 Pa; the average grain size of the magnet after sintering is ≤6μm.
[0022] The present invention adopts a low-temperature and long-time sintering process to refine the grains, so that the coercive force of the magnets with the same component ratio is improved; if the temperature is too high, it will cause abnormal growth of the grains.
[0023] Preferably, (4) the black sheet treatment comprises machining the sintered magnet into a black sheet and performing surface treatment, wherein the surface treatment comprises one or more of acid washing, alkali washing, sand blasting and laser polishing.
[0024] Preferably, the diffusion source in (4) comprises a diffusion source alloy powder, an organic solvent, and a photocuring agent in a mass ratio of (5-30):(1-8):1.
[0025] More preferably, the diffusion source in the diffusion source diffusion comprises a diffusion source alloy powder, an organic solvent, and a photocuring agent in a mass ratio of (11-18):(2-5):1.
[0026] More preferably, the diffusion source alloy powder is Dy a2 M 1-a2 Alloy, Tb b2 M 1-b2 One or more of, M is one or more of Fe, Ga, Cu, Al, Co, 0.6≤a2≤1, 0.6≤b2≤1;
[0027] The organic solvent includes one or more of ethanol, polyvinyl alcohol, benzyl alcohol, and ethylene glycol;
[0028] The photocuring agent is a cationic photoinitiator, including one or more of diazonium salts, diaryliodonium salts, triarylsulfonium salts, alkylsulfonium salts, iron arene salts, sulfonyloxy ketones, and triarylsiloxane ethers.
[0029] Preferably, the diffusion source diffusing in (4) includes coating the diffusion source on a black sheet, curing and drying the black sheet by irradiation with light having a wavelength of 250-800 nm.
[0030] More preferably, the wavelength is 250~450nm.
[0031] More preferably, the irradiation curing time is 1 to 30 minutes.
[0032] Further preferably, after the diffusion source is applied, the weight of the black sheet increases by 0.6-0.8 wt%.
[0033] Preferably, the diffusion temperature in the diffusion heat treatment in (4) is 850-950°C, the diffusion time is 10-20h, and the vacuum degree is less than 10 -3 Pa.
[0034] Preferably, the aging temperature in (4) is 360-650°C, and the aging time is 2-12h.
[0035] Preferably, the method for preparing the grain boundary diffusion sintered NdFeB permanent magnet material comprises:
[0036] (1) The main alloy is mixed according to the following chemical formula [(Pr 0.25 Nd 0.75 ) x1 (LR) y1 (HR) 1-x1-y1 ] a1 (TM) b1 (HM) c1 B d1 Fe 100-a1-b1-c1-d , wherein 0.7≤x1≤1, 0≤y1≤0.3, 29.5≤a1≤30.5, 0<b1≤5, 0<c1≤0.3, 0.92≤d1≤0.98, LR is one or more of the light rare earth elements La, Ce, and Y, HR is one or more of the heavy rare earth elements Dy, Tb, Gd, and Ho, TM is one or more of Al, Cu, Co, Mn, and Ga, and HM is one or more of Nb, Zr, Hf, Ti, and V;
[0037] The main alloy after proportioning is melted, cast and spun, the melting temperature is 1485~1505℃, the casting temperature is 1415~1465℃, and the thickness of the main alloy spun sheet is 0.15~0.45mm;
[0038] The main alloy flakes are placed in a hydrogen crushing furnace to be hydrogen crushed into main alloy coarse powder, and then the main alloy fine powder is obtained by air flow grinding under the protection of inert gas; the average particle size of the main alloy fine powder is 3.8~4.3μm;
[0039] (2) The auxiliary alloy is mixed according to the following chemical formula: Pr x2 (Ga a2 Al b2 Ti 1-a2-b2 ) 1-x2 Ratio, where 0.3≤x2≤0.9, 0.1≤a2≤0.7, 0≤b2≤0.5;
[0040] The auxiliary alloy after proportioning is melted, cast and spun, the melting temperature is 1485~1505℃, the casting temperature is 1415~1465℃, and the thickness of the auxiliary alloy spun sheet is 0.15~0.45mm;
[0041] The auxiliary alloy flakes are placed in a hydrogen crushing furnace to be hydrogen crushed into auxiliary alloy coarse powder, and then the auxiliary alloy fine powder is obtained by air flow grinding under the protection of inert gas; the average particle size of the auxiliary alloy fine powder is 3.2~3.6μm;
[0042] (3) Mixing main alloy fine powder, auxiliary alloy fine powder and nano powder in a mass ratio of (90-99): (0.5-9.5): (0.1-0.5), adding an auxiliary agent and mixing evenly, and pre-pressing and forming under a magnetic field strength H>2000Gs; the nano powder is one or more of transition metal carbide nano powder and transition metal oxide nano powder;
[0043] (4) isostatically pressing the pre-pressed embryo body, the isostatic pressing pressure is 180~220Mpa, and the holding time is 5~60s;
[0044] (5) Then sintering is carried out, the sintering temperature is 1000~1070℃, the sintering time is 6~12h, and the vacuum degree is less than 5×10 - 2 Pa; the average grain size of the sintered magnet is ≤6μm;
[0045] (6) machining the sintered magnet into a black sheet, and performing surface treatment to obtain a surface-treated black sheet, wherein the surface treatment includes one or more of acid washing, alkali washing, sand blasting, and laser polishing;
[0046] (7) Mixing a diffusion source alloy powder, an organic solvent, and a light curing agent in a mass ratio of (5-30): (1-8): 1 to prepare a slurry, applying the slurry to a surface-treated black sheet, and then curing the slurry by irradiating light with a wavelength of 250-800 nm, and drying the slurry to obtain a diffused magnet;
[0047] The diffused magnet is transferred to a diffusion furnace with a diffusion temperature of 850-950°C, a diffusion time of 10-20 hours, and a vacuum degree of <10 -3 Pa;
[0048] (8) Then carry out aging, the aging temperature is 360~650℃, the aging time is 2~4h, and after the aging is completed, the furnace is immediately filled with inert gas and air-cooled to 60~80℃; thus, the grain boundary diffusion sintered NdFeB permanent magnet material is obtained.
[0049] More preferably, in the above (1), Al≤0.5, Ga≤0.3 in TM, and Nb+Zr≤0.1 in HM.
[0050] More preferably, in said (1), the temperature is raised for casting after the vacuum degree of the smelting furnace is ≤3 Pa; the oxygen content of the cast sheet is ≤150ppm, and the carbon content is ≤300ppm;
[0051] The dehydrogenation temperature in the hydrogen crushing furnace is 500~580℃, the hydrogen content of the main alloy coarse powder is ≤800ppm, and the oxygen content is ≤1000ppm;
[0052] The main alloy fine powder includes main alloy coarse powder and antioxidant in a mass ratio of 1: (0.5-1.2).
[0053] More preferably, the antioxidant is one or more of glycerol, zinc stearate, silicate, silicone oil and n-octane.
[0054] More preferably, in (2), 0.6≤x2≤0.8, 0.3≤a2≤0.5, and 0≤b2≤0.3.
[0055] More preferably, in said (2), the temperature is raised for casting after the vacuum degree of the smelting furnace is ≤3Pa; the oxygen content of the cast sheet is ≤150ppm, and the carbon content is ≤300ppm;
[0056] The dehydrogenation temperature in the hydrogen crushing furnace is 500~580℃, the hydrogen content of the auxiliary alloy coarse powder is ≤800ppm, and the oxygen content is ≤1000ppm;
[0057] The auxiliary alloy fine powder includes auxiliary alloy coarse powder and antioxidant in a mass ratio of 1: (0.5-1.2).
[0058] More preferably, the antioxidant is one or more of glycerol, zinc stearate, silicate, silicone oil and n-octane.
[0059] Further preferably, the transition metal carbide nanopowder in (3) includes one or more of niobium carbide (NbC), tantalum carbide (TaC), vanadium carbide (VC), zirconium carbide (ZrC), and tungsten carbide (WC); the transition metal oxide nanopowder includes one or more of ferrosoferric oxide, titanium dioxide (titanium dioxide), aluminum oxide, and zinc oxide.
[0060] More preferably, the nanopowder in (3) is a mixture of transition metal carbide nanopowder and transition metal oxide nanopowder.
[0061] More preferably, the mass ratio of the diffusion source alloy powder, the organic solvent, and the photocuring agent in (7) is (11-18): (2-5): 1.
[0062] More preferably, the diffusion source alloy powder is Dy a2 M 1-a2 Alloy, Tb b2 M 1-b2 One or more of, M is one or more of Fe, Ga, Cu, Al, Co and other elements, 0.6≤a2≤1, 0.6≤b2≤1;
[0063] The organic solvent includes one or more of ethanol, polyvinyl alcohol, benzyl alcohol, and ethylene glycol;
[0064] The photocuring agent is a cationic photoinitiator, including one or more of diazonium salts, diaryliodonium salts, triarylsulfonium salts, alkylsulfonium salts, iron arene salts, sulfonyloxy ketones, and triarylsiloxane ethers.
[0065] A grain boundary diffusion sintered NdFeB permanent magnet material with a thickness of 1-10 mm and a Hcj of 20-33 kOe.
[0066] Preferably, the thickness of the grain boundary diffusion sintered NdFeB permanent magnet material is 8-10 mm, and the Hcj is 20-28 kOe.
[0067] Compared with the prior art, the present invention has the following beneficial effects:
[0068] 1. The present invention designs the magnet matrix composition of grain boundary diffusion sintered NdFeB permanent magnet material, forms a PrGa-rich grain boundary phase through the combination of main alloy and auxiliary alloy, and reduces the content of ferromagnetic elements in the grain boundary; and adds nanopowder to the magnet matrix to further increase the grain boundary width, thereby providing a diffusion channel for the subsequent preparation process, which is conducive to the development of large-size sintered NdFeB permanent magnet materials;
[0069] 2. In the grain boundary phase of the present invention, Ga tends to be distributed at the grain boundary, replacing the occupancy of Fe in the grain boundary, thereby reducing the ferromagnetism at the grain boundary; while Pr tends to be distributed on the surface of the main phase grains, and its corresponding 2:14:1 phase has a higher anisotropic field strength (Ha). The combined effect of the two helps to improve the magnetic properties of the base magnet, especially the coercive force;
[0070] 3. The present invention adds a photocuring agent to the diffusion source, and reduces the drying temperature of the drying tunnel through the photocuring process, thereby saving energy and improving the bonding strength of the diffusion source slurry on the surface of the black sheet magnet, which helps to improve the diffusion effect;
[0071] 4. The present invention can obtain sintered NdFeB permanent magnet materials with better comprehensive magnetic properties under the same performance substrate conditions or the same diffusion conditions, and is suitable for mass production;
[0072] 5. The preparation method of the grain boundary diffusion sintered NdFeB permanent magnet material of the present invention is suitable for large-size products with high magnetization direction (8 mm and above). BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 This is a cross-sectional metallographic image of the main alloy sheet in Example 1 of the present invention.
[0074] Figure 2 This is a cross-sectional metallographic image of the black sheet after surface treatment before diffusion in Example 1 of the present invention.
[0075] Figure 3 This is a cross-sectional metallographic image of the grain boundary diffusion sintered NdFeB permanent magnet material in Example 1 of the present invention. DETAILED DESCRIPTION
[0076] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0077] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means. Example 1
[0078] (1) Prepare the main alloy according to the chemical formula [(Pr 0.25 Nd 0.75 ) 0.9 Ce 0.08 Dy 0.02 ] 30.4 Al 0.5 Cu 0.1 Ga 0.1 Zr 0.05 Ti 0.05 Nb 0.05 B 0.94 Fe 67.81 Proportioning;
[0079] The main alloy after proportioning is added into the smelting furnace, the vacuum degree of the smelting furnace is ≤3Pa, the temperature is raised to 1495±5℃ for smelting, and the casting is performed at 1440±5℃ and then the sheet is spun; the oxygen content of the casting sheet is ≤100ppm, the carbon content is ≤150ppm, and the thickness of the main alloy sheet is 0.30mm; according to Figure 1 It can be seen that the microstructure of the shavings is well distributed in columnar crystals and has no other impurities;
[0080] The main alloy flakes were placed in a hydrogen crushing furnace for hydrogen crushing into main alloy coarse powder, and antioxidant zinc stearate was added (the mass ratio of main alloy coarse powder to antioxidant was 1:0.7), and main alloy fine powder was obtained by air flow grinding under nitrogen protection; the average particle size of the main alloy fine powder was 4.1μm;
[0081] (2) The auxiliary alloy is prepared according to the chemical formula Pr 0.65 (Ga 0.65 Al 0.2 Ti 0.15 ) 0.35 Proportioning; adding the proportioned auxiliary alloy into a smelting furnace, the vacuum degree of the smelting furnace is ≤3Pa, heating to 1495±5℃ for smelting, casting at 1430±5℃ and then throwing the sheet; the oxygen content of the casting sheet is ≤150ppm, the carbon content is ≤300ppm, and the thickness of the auxiliary alloy thrown sheet is 0.28mm;
[0082] The auxiliary alloy flakes were placed in a hydrogen crushing furnace to be hydrogen crushed into auxiliary alloy coarse powder, and antioxidant zinc stearate was added (the mass ratio of auxiliary alloy coarse powder to antioxidant was 1:0.7), and auxiliary alloy fine powder was obtained by air flow grinding under nitrogen protection; the average particle size of the auxiliary alloy fine powder was 3.4μm;
[0083] (3) After mixing 96 parts of main alloy fine powder, 3.7 parts of auxiliary alloy fine powder and 0.3 parts of niobium carbide nanopowder, 1 part of lubricant and 3 parts of aviation gasoline were added, the mixture was stirred for 80 minutes, and then sieved through a sieving machine to reduce the agglomeration of fine powder, and pre-pressed under a magnetic field intensity of H = 2700 Gs;
[0084] (4) The pre-pressed embryo is vacuum packaged and isostatically pressed at a pressure of 200 MPa for a holding time of 20 seconds;
[0085] (5) Then sintering is carried out at a sintering temperature of 1055°C, a sintering time of 8 h, and a vacuum degree of 3×10 -2 Pa; the average grain size of the magnet after sintering is ≤6μm;
[0086] (6) The sintered magnets are machined into black sheets of different specifications: 30*20*3.5 (mm), 30*20*5.5 (mm), 30*20*8.5 (mm), and then pickled and laser polished to obtain surface-treated black sheets;
[0087] (7) 75 parts of diffusion source alloy powder (TbCuAl alloy powder), 20 parts of organic solvent (anhydrous ethanol), and 5 parts of photocuring agent (cationic photoinitiator sulfonyloxy ketone) were mixed to make a slurry, and then applied to the surface-treated black sheet, and the weight of the black sheet increased by 0.7wt%. The black sheet was then irradiated and cured with light of a wavelength of 250-450nm for 6min, and dried in a drying oven at 70℃ to obtain a diffused magnet. The diffused magnet was transferred to a diffusion furnace, and the diffusion temperature was 910℃, the diffusion time was 18h, and the vacuum degree was 2×10 -4 Pa;
[0088] (8) Then carry out aging, the aging temperature is 500℃, the aging time is 4h, and immediately fill the furnace with inert gas after the aging, and air cool to 60℃; thus, the grain boundary diffusion sintered NdFeB permanent magnet material is obtained.
[0089] Figure 1 is a cross-sectional metallographic image of the main alloy sheet in this embodiment; Figure 2 This is a cross-sectional metallographic image of the black sheet after surface treatment before diffusion in this embodiment, where +1 is a PrGa-rich grain boundary phase; Figure 3 This is a cross-sectional metallographic image of the grain boundary diffusion sintered NdFeB permanent magnet material in this embodiment.
[0090] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this embodiment are shown in Table 1. Example 2
[0091] (1) Prepare the main alloy according to the chemical formula [(Pr 0.25 Nd 0.75 ) 0.9 Ce 0.08 Dy 0.02 ] 30.4 Al 0.5 Cu 0.1 Ga 0.1 Zr 0.05 Ti 0.05 Nb 0.05 B 0.94 Fe 67.81 Proportioning;
[0092] The main alloy after proportioning is added into a smelting furnace, the vacuum degree of the smelting furnace is ≤3Pa, the temperature is raised to 1495±5℃ for smelting, and the casting is performed at 1440±5℃ and then the sheet is spun; the oxygen content of the casting sheet is ≤150ppm, the carbon content is ≤200ppm, and the thickness of the main alloy spun sheet is 0.30mm; the microstructure of the spun sheet has good columnar crystal distribution and no other impurities;
[0093] The main alloy flakes were placed in a hydrogen crushing furnace for hydrogen crushing into main alloy coarse powder, and antioxidant zinc stearate was added (the mass ratio of main alloy coarse powder to antioxidant was 1:0.7), and main alloy fine powder was obtained by air flow grinding under nitrogen protection; the average particle size of the main alloy fine powder was 4.1μm;
[0094] (2) The auxiliary alloy is prepared according to the chemical formula Pr 0.65 (Ga 0.65 Al 0.2 Ti 0.15 ) 0.35 Proportioning; adding the proportioned auxiliary alloy into a smelting furnace, the vacuum degree of the smelting furnace is ≤3Pa, heating to 1495±5℃ for smelting, casting at 1430±5℃ and then throwing the sheet; the oxygen content of the casting sheet is ≤150ppm, the carbon content is ≤300ppm, and the thickness of the auxiliary alloy thrown sheet is 0.28mm;
[0095] The auxiliary alloy flakes were placed in a hydrogen crushing furnace to be hydrogen crushed into auxiliary alloy coarse powder, and antioxidant zinc stearate was added (the mass ratio of auxiliary alloy coarse powder to antioxidant was 1:0.7), and auxiliary alloy fine powder was obtained by air flow grinding under nitrogen protection; the average particle size of the auxiliary alloy fine powder was 3.4μm;
[0096] (3) After mixing 96 parts of main alloy fine powder, 3.7 parts of auxiliary alloy fine powder and 0.3 parts of niobium carbide nanopowder, 1 part of lubricant and 3 parts of aviation gasoline were added, the mixture was stirred for 80 minutes, and then sieved through a sieving machine to reduce the agglomeration of fine powder, and pre-pressed under a magnetic field intensity of H = 2600 Gs;
[0097] (4) The pre-pressed embryo is vacuum packaged and isostatically pressed at a pressure of 200 MPa for a holding time of 20 seconds;
[0098] (5) Then sintering is carried out at a sintering temperature of 1065°C, a sintering time of 8 h, and a vacuum degree of 3×10 -2 Pa; the average grain size of the magnet after sintering is ≤6μm;
[0099] (6) The sintered magnets are machined into black sheets of different specifications: 30*20*3.5 (mm), 30*20*5.5 (mm), 30*20*8.5 (mm), and then pickled and laser polished to obtain surface-treated black sheets;
[0100] (7) 75 parts of diffusion source alloy powder (TbCuAl alloy powder), 20 parts of organic solvent (anhydrous ethanol), and 5 parts of photocuring agent (cationic photoinitiator sulfonyloxy ketone) were mixed to make a slurry, and then applied to the surface treated black sheet, and the weight of the black sheet increased by 0.65wt%. The black sheet was then irradiated with light with a wavelength of 250-450nm for 7 minutes and dried in a drying oven at 70℃ to obtain a diffused magnet. The diffused magnet was transferred to a diffusion furnace, and the diffusion temperature was 910℃, the diffusion time was 25h, and the vacuum degree was 2×10 -4 Pa;
[0101] (8) Then, aging is carried out at a temperature of 490°C for 6 hours. After the aging is completed, the furnace is immediately filled with inert gas and air-cooled to 60°C. Thus, the grain boundary diffusion sintered NdFeB permanent magnet material is obtained.
[0102] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this embodiment are shown in Table 1. Example 3
[0103] Compared with Example 1, the difference is that in (3), 95 parts of main alloy fine powder, 4.3 parts of auxiliary alloy fine powder, 0.4 parts of niobium carbide nanopowder, and 0.3 parts of ferroferric oxide nanopowder are mixed, and then 1 part of lubricant and 3 parts of aviation gasoline are added.
[0104] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this embodiment are shown in Table 1. Example 4
[0105] Compared with Example 1, the difference is that in (3), 93 parts of main alloy fine powder, 6.2 parts of auxiliary alloy fine powder, 0.3 parts of titanium dioxide nanopowder, and 0.5 parts of niobium carbide nanopowder are mixed, and then 1 part of lubricant and 3 parts of aviation gasoline are added.
[0106] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this embodiment are shown in Table 1. Example 5
[0107] Compared with Example 1, the difference is that in (1), the main alloy is prepared according to the chemical formula [(Pr 0.25 Nd 0.75 ) 0.9 Ce 0.08 Dy 0.02 ] 30.4 Al 0.6 Cu 0.1 Ga 0.1 Zr 0.3 Ti 0.15 Nb 0.05 B 0.94 Fe 67.36 Make the proportions.
[0108] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this embodiment are shown in Table 1. Comparative Example 1
[0109] Compared with Example 1, the difference is that no nano powder is added.
[0110] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this comparative example are shown in Table 1. Comparative Example 2
[0111] Compared with Example 1, the difference is that the auxiliary alloy has the chemical formula Pr 0.65 Ga 0.35 Ratio.
[0112] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this comparative example are shown in Table 1. Comparative Example 3
[0113] Compared with Example 1, the difference is that no auxiliary alloy fine powder is added. In (3), 99.3 parts of main alloy fine powder, 0.4 parts of niobium carbide nanopowder, and 0.3 parts of ferroferric oxide nanopowder are mixed, and then 1 part of lubricant and 3 parts of aviation gasoline are added.
[0114] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this comparative example are shown in Table 1. Comparative Example 4
[0115] Compared with Example 1, the difference is that in (3), 95 parts of main alloy fine powder, 3.5 parts of auxiliary alloy fine powder, 1 part of niobium carbide nanopowder, and 0.5 part of ferrosoferric oxide nanopowder are mixed, and then 1 part of lubricant and 3 parts of aviation gasoline are added.
[0116] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this comparative example are shown in Table 1. Comparative Example 5
[0117] Compared with Example 1, the difference is that the diffusion source in (7) includes 75 parts of diffusion source alloy powder (TbCuAl alloy powder) and 25 parts of organic solvent (anhydrous ethanol).
[0118] The properties of the grain boundary diffusion sintered NdFeB permanent magnet material prepared in this comparative example are shown in Table 1.
[0119] Table 1. Performance data of grain boundary diffusion sintered NdFeB permanent magnet materials
[0120]
[0121] It can be seen from the above table that the preparation method of the grain boundary diffusion sintered NdFeB permanent magnet material of the present invention can significantly improve the magnetic properties of the grain boundary diffusion sintered NdFeB permanent magnet material, and can still maintain relatively high comprehensive magnetic properties for large-sized sintered NdFeB permanent magnet materials.
[0122] In Comparative Example 1, no nanopowder is added, resulting in limited diffusion channels of sintered NdFeB permanent magnet materials, decreased coercive force increase after diffusion, and especially large-size products with coercive force 0.8~1kOe lower than that in Example 1; in Comparative Example 4, there is too much nanopowder, and the volume fraction of non-main phase increases, resulting in a significant decrease in remanence, which is 0.1~0.2kGs lower than that in Example 1; in Example 5, the main alloy ratio is changed, resulting in the substrate ratio not meeting the requirements of Al≤0.5 and Nb+Zr≤0.1, so that the diffusion effect is limited, and the coercive force increase of the magnet is 1~1.5kOe lower than that in Example 1; in Comparative Example 2, the ratio of the auxiliary alloy is changed, and the elements Al and Ti are not added, resulting in an increase in the proportion of ferromagnetic phase in the grain boundary phase composition, which is not conducive to the increase in the coercive force of the diffused thick product; in Comparative Example 3, no auxiliary alloy is added, resulting in low substrate magnetic properties and low coercive force of the product after diffusion; in Comparative Example 5, no photocuring agent is added, resulting in a decrease in the bonding strength between the diffusion slurry and the substrate material, and a poor diffusion effect.
[0123] In summary, the present invention designs the composition of grain boundary diffusion sintered NdFeB permanent magnet materials, forms a PrGa-rich grain boundary phase through the combination of the main alloy and the auxiliary alloy, and reduces the content of ferromagnetic elements in the grain boundaries; and adds nanopowder to the matrix to further increase the grain boundary width, thereby providing a diffusion channel for subsequent processes, which is conducive to the development of large-size sintered NdFeB permanent magnet materials.
[0124] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A method for preparing a grain boundary diffusion sintered NdFeB permanent magnet material, characterized in that: The preparation method comprises: (1) Main alloy proportioning, smelting, and powdering to obtain main alloy fine powder; the chemical formula of the main alloy is [(Pr 0.25 Nd 0.75 ) x1 (LR) y1 (HR) 1-x1-y1 ] a1 (TM) b1 (HM) c1 B d1 Fe 100-a1-b1-c1-d , wherein 0.7≤x1≤1, 0≤y1≤0.3, 29.5≤a1≤30.5, 0<b1≤5, 0<c1≤0.3, 0.92≤d1≤0.98, LR is one or more of the light rare earth elements La, Ce, and Y, HR is one or more of the heavy rare earth elements Dy, Tb, Gd, and Ho, TM is one or more of Al, Cu, Co, Mn, and Ga, and HM is one or more of Nb, Zr, Hf, Ti, and V; (2) Proportioning, smelting and powdering the auxiliary alloy to obtain auxiliary alloy fine powder; the chemical formula of the auxiliary alloy is Pr x2 (Ga a2 Al b2 Ti 1-a2-b2 ) 1-x2 , where 0.3≤x2≤0.9, 0.1≤a2≤0.7, 0≤b2≤0.5; (3) mixing the main alloy fine powder, the auxiliary alloy fine powder and the nano powder, adding an additive and pre-pressing to obtain a pre-pressed embryonic body; the nano powder is one or more of transition metal carbide nano powder and transition metal oxide nano powder; (4) The pre-pressed embryo is subjected to isostatic pressing, sintering, black sheet treatment, diffusion source diffusion, diffusion heat treatment, and aging to obtain grain boundary diffusion sintered NdFeB permanent magnet material.
2. The method for preparing the grain boundary diffusion sintered NdFeB permanent magnet material according to claim 1, characterized in that: In the above (1), Al≤0.5, Ga≤0.3 in TM, and Nb+Zr≤0.1 in HM.
3. The method for preparing the grain boundary diffusion sintered NdFeB permanent magnet material according to claim 1, characterized in that: The mass ratio of the main alloy fine powder, the auxiliary alloy fine powder and the nano powder in (3) is (90-99): (0.5-9.5): (0.1-0.5).
4. The method for preparing the grain boundary diffusion sintered NdFeB permanent magnet material according to claim 1, characterized in that: The transition metal carbide nanopowder in (3) includes one or more of niobium carbide, tantalum carbide, vanadium carbide, zirconium carbide, and tungsten carbide; the transition metal oxide nanopowder includes one or more of ferroferric oxide, titanium dioxide, aluminum oxide, and zinc oxide.
5. The method for preparing the grain boundary diffusion sintered NdFeB permanent magnet material according to claim 1, characterized in that: The auxiliary agent in (3) includes one or more of lubricants, aviation gasoline, and antioxidants.
6. The method for preparing the grain boundary diffusion sintered NdFeB permanent magnet material according to claim 1, characterized in that: The static pressure in (4) is 180~220Mpa, and the holding time is 5~60s; the sintering temperature in (4) is 1000~1070℃, the sintering time is 6~12h, and the vacuum degree is less than 5×10 -2 Pa; the average grain size of the magnet after sintering is ≤6μm.
7. The method for preparing the grain boundary diffusion sintered NdFeB permanent magnet material according to claim 1, characterized in that: The diffusion source in (4) comprises a diffusion source alloy powder, an organic solvent, and a photocuring agent in a mass ratio of (5-30): (1-8): 1; the diffusion source alloy powder is Dy a2 M 1-a2 Alloy, Tb b2 M 1-b2 One or more of, M is one or more of Fe, Ga, Cu, Al, Co elements, 0.6≤a2≤1, 0.6≤b2≤1; the organic solvent includes one or more of ethanol, polyvinyl alcohol, benzyl alcohol, and ethylene glycol; the photocuring agent is a cationic photoinitiator, including one or more of diazonium salts, diaryl iodonium salts, triaryl sulfonium salts, alkyl sulfonium salts, iron arene salts, sulfonyloxy ketones, and triaryl siloxane ethers.
8. The method for preparing the grain boundary diffusion sintered NdFeB permanent magnet material according to claim 1, characterized in that: The diffusion source diffusion in (4) includes coating the diffusion source on the black sheet, curing and drying the diffusion source by irradiation with light having a wavelength of 250-800 nm; after coating the diffusion source, the weight of the black sheet increases by 0.6-0.8 wt%.
9. The method for preparing the grain boundary diffusion sintered NdFeB permanent magnet material according to claim 1, characterized in that: The diffusion temperature in the diffusion heat treatment in (4) is 850-950°C, the diffusion time is 10-20h, and the vacuum degree is less than 10 -3 Pa; the aging temperature in (4) is 360~650℃, and the aging time is 2~12h.
10. A grain boundary diffusion sintered NdFeB permanent magnet material obtained by the method for preparing grain boundary diffusion sintered NdFeB permanent magnet material according to claim 1, characterized in that: The grain boundary diffusion sintered NdFeB permanent magnet material has a thickness of 1-10 mm and a Hcj of 20-33 kOe.